2014
DOI: 10.3390/rs6054025
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Dimensional Index for Characterizing Crop Water Stress

Abstract: Abstract:The application of remotely sensed estimates of canopy minus air temperature (Tc-Ta) for detecting crop water stress can be limited in semi-arid regions, because of the lack of full ground cover (GC) at water-critical crop stages. Thus, soil background may restrict water stress interpretation by thermal remote sensing. For partial GC, the combination of plant canopy temperature and surrounding soil temperature in an image pixel is expressed as surface temperature (Ts). Soil brightness (SB) for an imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…In this work, we chose the TIGR database TIGR2002_v1.1 as the atmospheric data to execute the radiative transfer simulation procedure (see Section 2.5). However, it was found that TIGR2002_v1.1 is centred at low W values of less than 1.0 g/cm 2 . To obtain robust statistics, it is necessary to select different atmospheric profiles to make W uniformly distributed from dry to moist.…”
Section: Atmospheric Profile Datamentioning
confidence: 99%
See 3 more Smart Citations
“…In this work, we chose the TIGR database TIGR2002_v1.1 as the atmospheric data to execute the radiative transfer simulation procedure (see Section 2.5). However, it was found that TIGR2002_v1.1 is centred at low W values of less than 1.0 g/cm 2 . To obtain robust statistics, it is necessary to select different atmospheric profiles to make W uniformly distributed from dry to moist.…”
Section: Atmospheric Profile Datamentioning
confidence: 99%
“…To obtain robust statistics, it is necessary to select different atmospheric profiles to make W uniformly distributed from dry to moist. Figure 2 shows the selected 126 atmospheric profiles in which the atmospheric temperature (T 0 ) in the lowest layer varies from 232.25 K to 311.95 K and W varies from 0.09 g/cm 2 to 6.15 g/cm 2 , which represent worldwide atmospheric conditions with a moderate sample number and ensure that there is a nearly uniform distribution for W. Ninety-eight profiles (referred to as TIGR_98) were used for development of the LST retrieval algorithm and twenty-eight (referred to as TIGR_28) were used for validation. for the selected atmospheres.…”
Section: Atmospheric Profile Datamentioning
confidence: 99%
See 2 more Smart Citations
“…It generally occurs due to a decline in leaf turgor and atmospheric vapor pressure along with root-generated chemical signals causing a measurable reduction of leaf stomatal conductance to water vapor [4] and transpiration rate. The decrease in evaporative cooling causes an increase of vegetation temperature that can be tracked using thermal imagery [5,6]. The relationship between vegetation temperature and transpiration rates is affected by water stress experienced by the plants but also by environmental parameters, as the vapor pressure deficit of the air (VPD).…”
Section: Introductionmentioning
confidence: 99%